2012
DOI: 10.1088/0957-0233/23/8/085006
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent sampling for the measurement of structured surfaces

Abstract: Abstract. Uniform sampling in metrology has known drawbacks such as coherent spectral aliasing and a lack of efficiency in terms of measuring time and data storage. The requirement for intelligent sampling strategies has been outlined over recent years, particularly where the measurement of structured surfaces is concerned. Most of the present research on intelligent sampling has focused on dimensional metrology using coordinate-measuring machines with little reported in the area of surface metrology. In the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…The analysed adaptive sampling is the triangular patch sampling since it has achieved good reconstruction performances in Wang et al (2012) and Shih et al (2008). The reconstruction is performed through the piecewise cubic interpolation implemented in the fit function of MATLAB ® (2014).…”
Section: Reconstruction Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysed adaptive sampling is the triangular patch sampling since it has achieved good reconstruction performances in Wang et al (2012) and Shih et al (2008). The reconstruction is performed through the piecewise cubic interpolation implemented in the fit function of MATLAB ® (2014).…”
Section: Reconstruction Resultsmentioning
confidence: 99%
“…A review of intelligent sampling techniques can be found in Wang et al (2012). Among the reviewed techniques, two adaptive sampling methods have been analysed: triangle and rectangle patch adaptive subdivision.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many filtering and decomposition algorithms for freeform surfaces that are represented by triangular meshes were proposed. Those algorithms use different principles such as partial differential equations, lifting wavelets, mesh relaxation schemes, morphological operations and manifold harmonics, to filter any freeform surface or decompose it into its different scales and components [4][5][6][7][8][9][10]. The work carried out in this paper continues the previous work by investigating the two remaining blocks in figure 1, i.e., the texture representation and the parameter calculation.…”
Section: Introductionmentioning
confidence: 88%
“…Consequently, surface texture characterisation has witnessed important shifts in the last decade or two; from profile measurements to areal measurements and from simple surfaces to complex freeform surfaces [1][2][3]. These shifts have triggered the need for new algorithms and techniques that can better describe, represent, measure and characterise the newly evolved complex freeform surfaces [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [32] has made a summary about surface measurement, among which the probing points by uniform equidistant distribution in terms of the arc length is one of the most widely used method. Certainly, increasing the sample size can also reduce the uncertainty of an approximation model.…”
Section: 4mentioning
confidence: 99%